Pengaruh penerapan LKS laboratorium virtual melalui model pembelajaran inkuiri terbimbing terhadap pencapaian kompetensi siswa kelas X SMA Pertiwi 1 Padang - wahyu dilla abdullah; Hidayati Hidayati; Yenni Darvina; Masril Masril (PILLAR OF PHYSICS EDUCATION, 2019)
Understanding students' concepts of physics are still relatively low. This is because learning is not yet fully accompanied by practical activities, there are no guidelines in the implementation of practicum and the learning model used by teachers is less able to invite and guide students in finding and solving physics problems. To overcome these problems, researchers applied virtual laboratory worksheets through a guided inquiry learning model. The purpose of this study was to determine the effect of the application of virtual laboratory worksheets through guided inquiry learning models towards the achievement of competency in class X of Pertiwi 1 High School Padang. This type of research is pre-experimental design with the research design of One Group Pretest Posttest Design. The population in the study was all X MIA classes at Pertiwi 1 High School in Padang academic year 2018/2019. The sample in the X MIA 3 class study was selected using a purposive sampling technique. The assessment instruments used included attitude competencies with observation sheets, knowledge competencies through written tests and skills competencies with performance sheets. Analysis of the data used is regression and correlation tests for knowledge and skills competencies and descriptive for attitude competencies. The results of this study indicate that for attitudinal competence the average student experiences an increase every week. Knowledge competency has increased after being given treatment with a percentage of its influence of 63.77%. While the skills competency percentage effect is 25.13%. So that it can be concluded that there is a significant effect on the application of virtual laboratory worksheets through a guided inquiry learning model towards the competence of class X students at Pertiwi 1 High School Padang.